Effect of nitrogen application and Rhizobium inoculation on yield and nutrient uptake in lucerne (Medicago sativa)" - TUFENKCI, S; ERMAN, M; SONMEZ, F (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was conducted during 2002 and 2003 in Van, Turkey, to determine the effects of Rhizohiuirz inoculation and different levels of nitrogen on the yield and nutrient uptake of lucerne (hledicngo srrtivrr). Nitrogen festilization had significant effects on the plant height, the fresh forage and hay yields, and the nitrogen, phosphorus and potassiunl content of plant. The highest plant height, fresh forage and hay yields andnirogen content were obtained under treatment 120 kg N/ha. Phosphorus and potassium content of plant increased up to the level of 90 kg N/ha application and then decreased as nitrogen increased. Inoculation did not significantly affect any of the components measured, as the soil contained a sufficient and efficient native rhizobial population during both seasons.